EFFECT OF PRE-TREATMENTS ON CHEMICAL AND SENSORY QUALITIES OF DEHYDRATED RED ONION SLICES - R. SHIVANAND; K. LAXMAN; P. RAVI (The Bioscan, 2015)
An investigation was conducted to study the effect of pre-treatments on chemical and sensory qualities of dehydrated red onion slices. Results indicated that, the ascorbic acid content of the dehydrated red onion slices was found maximum (11.33 mg/100 g) in the samples pre-treated with 0.5 per cent KMS at 3 month after storage (MAS). The maximum reducing sugar (14.70%) and total sugar (25.65%) retention of dehydrated red onion slices were found in the samples pre-treated with 0.5 per cent sodium metabisulphite + 0.5 per cent citric acid at 3 MAS. With regards to organoleptic characters, the maximum score for colour and appearance (4.05), taste and flavour (4.12) and overall acceptability (4.15) were recorded in the slices pre-treated with 0.5 per cent sodium metabisulphite + 0.5 per cent citric acid, respectively. However, the lowest ascorbic acid (8.97 mg/100g), reducing sugar (11.33%) and total sugar (19.90%) content were noticed in control at 3 MAS. The lowest mean scores were recorded for colour and appearance (2.71)in the sample pretreated with 0.5 per cent KMS. Whereas, the lowest mean scores were recorded for taste and flavour (2.75) and overall acceptability (2.85) in control at 3 MAS. The onion slices pre-treated with 0.5 per cent sodium metabisulphite + 0.5 per cent citric acid had recorded the better results for the chemical characters and organoleptic traits.